A Clustering Algorithm Based on Rough Set and Genetic Algorithm - Yushu Xiong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
With the development of computer and information technology, the capacity of data and information is increasing. The processing of data and information becomes the hot issue in the current scientific community. Rough set and genetic algorithm are two data mining and processing technologies which had been commonly used. Rough set can process data quickly and the algorithm is simple. The convergence of genetic algorithm is fast and the robustness is good. This paper puts forward the effective clustering algorithm based on  the combined control of rough set and genetic algorithm, then does simulation experiment of segmentation images by  numerical simulation based on matlab programming, finally gets  the curve of calculation process and the effect diagram of image segmentation , verifies the effectiveness of the algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3407